O conceito de dinheiro em Marx - Bergmann, Luiz Felipe (2022)
Marx’s Concept of Money that is the result of a research about the money concept developed by Marx and presented in his work The Capital and in The Economic and Philosophic Manuscripts from 1857 to 1858. The motivations that led us to this study are a result of the divergences that the concept arises among the academics. The author’s writing, in many parts of his work, leads us to the conclusion that money is a commodity once it is determined as physical form. Furthermore, Marx stated that when money is introduced to the worldwide marketing it reassumes its original form as bars of precious metals, especially gold ones, also that only by being in the worldwide circulation, money works richly as a commodity. Some expositors conclude from the author’s text that money is not a commodity but, for some, it is considered a form with a material support and for others, a pure form. But there are the ones who conclude that, effectively, for Marx money is a commodity once it is determined in a physical instance. The divergences increased after dollar convertibility to gold being abandoned by the United States of America in 70’s of the last century due to the parity stablished in the Breton Woods Agreement signed after the Second World War. Our studies led us to conclude that the expositors who comprehend the money as a commodity do so in accordance with the concept expressed by Marx. Due to it we have concentrated our attention on the fundamentals of the expositors who adopted this conception of money and throughout the text their considerations will be presented. We started the study exposition by presenting a brief money history, since its first signals registered in history, as the coming and developing of the value awareness, this is one of the main elements for the money constitution due to its main function that is to serve as a value measurement. The solid ground of the concept of money as a commodity is, among the expositors, established in Antunes’ and Germer’s studies.